Modern Teaching Tendencies of Critical Thinking Forming of University Students - Gayazov, Alfis S.; Zamaletdinova, Gulnara F.; Amirov, Artur F.; Kostryukov, Andrey V.; Tikhomirova, Evgeniya I. (International Review of Management and Marketing, 2016)
The significance of the research problem is conditioned by the influence of global mass media on personality, providing it a unique ability to access information from anywhere in the world. To achieve the state when the identity of the student can feel confident in the process of choice and decision making, it is important to teach students the skills of critical thinking. In this regard, this paper is aimed to identify trends in didactic and pedagogical solutions to the problem. A leading research method is a constructive monitoring that allows using for the concept of "critical thinking" of the modern sense, due to the characteristics of the global information environment. The paper reveals the typology of thinking, the structure and content of its kinds; reveals peculiarities of process of formation of students' critical thinking, defining transformations of the learning content (interdisciplinary units) and learning technologies (interactive, design, computer); justifies the set of didactic tendencies of forming of students' critical thinking. Productivity of the revealed complex of didactic tendencies for students' critical thinking formation is proved. The paper submissions can be useful for teachers, listeners of the system of qualification's improvement and retraining of teachers, methodologists, post-graduates and University students. Keywords: Critical Thinking, Teaching Strategy, Global Information Environment, Structural Monitoring. JEL Classifications: I21, I25, I28